2022
DOI: 10.32718/nvlvet-f9701
|View full text |Cite
|
Sign up to set email alerts
|

Production of thin film of multicomponent inorganic semiconductors under quasi-equilibrium conditions

Abstract: Issues of improving the properties of semiconductor thin film and their reproducibility, as well as improving and reducing the cost of manufacturing technology stimulate research and development of new, advanced methods. Therefore, it is important to optimize the technology of getting reproducible, competitive, high-tech thin films of multicomponent semiconductor compounds with predetermined properties. In the given article it is shown that constructive and technological improvements of a method of thermal spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…One of the most used methods for depositing semiconductor thin films is thermal vacuum sputtering (Bunshah, 1994;Seshan, 2002;Frey & Khan, 2015;Ghanbari & Salavati-Niasari, 2021). The deposition of multicomponent thin films of chalcogenide semiconductors, linear polyacenes, metallophthalocyanines, as well as transparent upper copper iodide electrodes in our research was carried out in serial vacuum sputtering units of previous generations, such as URM 3.279.011 with a steam-oil high-vacuum pump and URM 3.279.047 with a highvacuum ion-heter pump, as well as in a modern combined installation of vacuum sputtering of thin films manufactured by the company "Torr International" (USA) accord-ing to previously described methods , 2020, 2022. It has been experimentally confirmed that high-quality films of organic semiconductors and copper iodide without heterogeneous inclusions, with properties close to single crystals, are deposited at low sputtering speeds.…”
Section: Methodsmentioning
confidence: 99%
“…One of the most used methods for depositing semiconductor thin films is thermal vacuum sputtering (Bunshah, 1994;Seshan, 2002;Frey & Khan, 2015;Ghanbari & Salavati-Niasari, 2021). The deposition of multicomponent thin films of chalcogenide semiconductors, linear polyacenes, metallophthalocyanines, as well as transparent upper copper iodide electrodes in our research was carried out in serial vacuum sputtering units of previous generations, such as URM 3.279.011 with a steam-oil high-vacuum pump and URM 3.279.047 with a highvacuum ion-heter pump, as well as in a modern combined installation of vacuum sputtering of thin films manufactured by the company "Torr International" (USA) accord-ing to previously described methods , 2020, 2022. It has been experimentally confirmed that high-quality films of organic semiconductors and copper iodide without heterogeneous inclusions, with properties close to single crystals, are deposited at low sputtering speeds.…”
Section: Methodsmentioning
confidence: 99%
“…In previous reviews 2020;2022), we provided an analysis of existing methods of applying thin films of inorganic semiconductor materials. In recent decades, thin films of organic semiconductors (OS), or, as they are also called, organic molecular crystals, have attracted special attention in connection with a number of proposals for their use in functional units of modern electronics, and therefore in modern technological equipment.…”
Section: Introductionmentioning
confidence: 99%